Water footprint as a sustainable water use indicator in spring area of pantanal biome, Brazil - Fagundes, Eliane Aparecida Antunes; Dantas Neto, José; Silva, Vicente Paulo Rodrigues; Barbosa, Domingos Sávio; Lima, Vera Lúcia Antunes (Ciência e Natura, 2022)
Water footprint (WF) is an indicator of fresh water consumption that considers in its calculation the used water volume during the production process. The research objective was to evaluatecotton, corn and soybean crops WF at the São Lourenço-MT sub-basin area. The water consumption was quantified in Green Water Footprint (WFGreen) and Gray Water Footprint (WFGray). The WFGreen of each crop was calculated by the evapotranspiration value throughout the crop growing period. The WFGray was counted separately for a group of nine agrochemicals. In the current scenario there is sustainability in the sub-basin of the São Lourenço river, but with the agricultural current area expansion rate, in 2025 there will be no such sustainability.